Science Curriculum Analysis in Terms of Sustainable Development Goals in Jordan - Altawalbeh, Khitam; Tawalbeh, Hadi (Scientia Publica Media, 2025)
This study investigates the integration of Sustainable Development Goals (SDGs) within the science curriculum for grades one through eight, examining the extent to which social, ecological, and economic dimensions of sustainability are represented. Employing a descriptive qualitative approach, the research utilizes content analysis as its primary methodology. A specifically designed content analysis card served as the instrument to systematically analyze the science curricula for each grade level. The analysis revealed a significant gap in SDG inclusion, with 43 out of the 96 recognized SDGs entirely absent from the curriculum. Furthermore, the study’s findings highlight a strong emphasis on the environmental dimension of sustainable development. This dimension dominated the curriculum content related to SDGs, registering a frequency of 765 instances and accounting for 39.11% of all SDG-related content. While environmental sustainability was clearly prioritized, social and economic aspects of the SDGs received considerably less attention. In terms of grade-level distribution, the sixth-grade science curriculum demonstrated the highest degree of SDG integration, featuring 642 instances of SDG inclusion, representing 32.82% of the total. Conversely, the eighth-grade science curriculum exhibited the lowest level of SDG incorporation, with only 70 instances (3.58%). This disparity across grade levels suggests inconsistencies in the curriculum’s approach to sustainable development education. Based on these findings, the study proposes a series of recommendations aimed at enhancing the integration of all three dimensions of sustainable development (social, ecological, and economic) across all grade levels within the science curriculum. These recommendations seek to address the identified gaps and promote a more comprehensive and balanced approach to sustainability education, ensuring that students develop a holistic understanding of the SDGs and their interconnectedness. Further research could explore the pedagogical approaches used to teach these SDGs and assess student understanding of sustainable development concepts.